Mechanical Properties and Microstructure of Reinforced Passivation Film: A Reactive Molecular Dynamics Study - Wang, Lanqin; Li, Mengmeng; Li, Zhipeng; Xu, Xiaoqian; Wang, Muhan; Wang, Pan; Hu, Xiaoxia; Zhang, Yue; Wang, Xinpeng (Frontiers in Materials, 2020)
Reinforced concrete is one of the most critical composite material in the modern civil engineering and can improve the tensile resistance of cement-based concrete, and its passivation film plays an important role in the durability of concrete and preventing steel corrosion. But, due to the size limitations, the destruction of micro-scale steel bars has not been well studied. In this work, the reactive molecular dynamics simulation was employed to studying the mechanical properties of steel and its passivation film. The uniaxial stretching of different compounds of γ-FeOOH, γ-Fe2O3 and Fe was performed. We found that the oxidation can reduce the tensile strength of steel. For the three compounds of γ-FeOOH, γ-Fe2O3 and Fe, the order of tensile strength from high to low is Fe>γ-Fe2O3>γ-FeOOH. But, the ductility of γ-FeOOH under x direction is increased. The detail microstructure analysis shown that the difference of tensile strength is origin from the coordination in the materials. The two kinds of stretching processes of whole system stretching (in the Fe phase and x direction of γ-FeOOH phase) and partly area stretching (in the Fe2O3 phase and z direction of γ-FeOOH phase) were clarified. The external force is dispersed in whole system stretching but opposite in partly area stretching. This investigation leads to possible new direction for studying the tensile strength of materials, and the strategy of evaluating materials tensile strength can supply valuable information in evaluating and improving the mechanical properties of reinforced concrete.